In-Memory Computation Based Mapping of Keccak-f Hash Function - Kingra, Sandeep Kaur; Parmar, Vivek; Suri, Manan (Frontiers in Nanotechnology, 2022)
Cryptographic hash functions play a central role in data security for applications like message authentication, data verification and detecting malicious or illegal modification of data. However, such functions typically require intensive computations with high volume of memory accesses. Novel computing architectures such as Logic-in-Memory (LIM)/In-Memory Computing (IMC) have been investigated in literature to address the limitations of intense compute and memory bottleneck. In this work, we present an implementation of Keccak-f (a state-of-the-art secure hash algorithm) using a variant of Simultaneous Logic-in-Memory (SLIM) that utilizes emerging non-volatile memory (NVM) devices. Detailed operation and instruction mapping on SLIM based digital gates is presented. Through simulations we benchmark the proposed approach using LIM cells based on four different emerging NVM devices (OxRAM, CBRAM, PCM, FeRAM). The proposed mapping strategy when used with state-of-the-art emerging NVM devices offers EDP savings of upto 300x compared to conventional methods.